Treatment of histoid leprosy: a lack of consensus. (16th June 2020) - Bartos, Gregory; Sheuring, Ryan; Combs, Angela; Rivlin, Daniel
Abstract: Histoid leprosy is a rare variant of leprosy with a unique clinical presentation and bacilli rich histology. These patients are large reservoirs for disease and vectors for spread, making prompt diagnosis and treatment crucial. To date, no consensus on treatment and duration exists. This paper aims to investigate the efficacy, safety, and duration of varying treatment regimens in patients with histoid leprosy. A systematic PubMed review of all articles published before January 2020 containing the key words histoid leprosy. All patients included must have completed their prescribed treatments with comment on outcomes and treatment duration. The review generated 165 articles containing 62 cases that met inclusion criteria. A majority of cases reported excellent clinical outcomes with limited adverse events. Regimens included variations of rifampicin, dapsone, clofazimine, minocycline, ofloxacin, and sulforthormadine with most treatment duration lasting 12 or 24 months. Existing literature is limited to case reports or case series and may be subject to publication bias of successful cases. Many reports lack quantifiable data regarding outcomes and rely on clinical judgment. Continued observation for complete clearance or relapse was limited. The findings demonstrate that multibacillary‐multidrug therapy is an efficacious and safe treatment for histoid leprosy. No significant differences were observed between 12 and 24 months of treatment. There remains no consensus on treatment duration for histoid leprosy.